Authoritarian legal harmonization in the post-Soviet space. Issue 7 (2nd October 2020) - Lemon, Edward; Antonov, Oleg
ABSTRACT: Faced with common threats to their regimes from independent civil society, organized opposition groups and protest movements, authoritarian governments in the former Soviet Union have learned from one another and adopted similar policies to consolidate their power. This article examines the process of authoritarian policy transfer in three fields: peaceful assembly, civil society and political participation, focusing on Russia, Kazakhstan, Kyrgyzstan, Tajikistan and Uzbekistan. The article examines the role played by the Commonwealth of Independent States- Inter-parliamentary Assembly, the body charged with legal harmonization in the former Soviet Union and ignored thus far by scholars of authoritarian diffusion. Through causal process tracing and the use of document comparison software, we compare 34 laws and decrees. Our findings indicate that diffusion is no illusion in the former Soviet Union. Autocrats have adopted similar legislation in all three fields, with the greatest degree of convergence in laws related to extremism, terrorism and operational searches, all of which are used to pursue political opponents. Russia is usually, but not always, the policy innovator. The region's poorest states – Kyrgyzstan and Tajikistan – both dependent on Russia in economic, political and security spheres display the highest levels of legal harmonization with the former Soviet centre.